Intraoperative Flurbiprofen Treatment Alters Immune Checkpoint Expression in Patients Undergoing Elective Thoracoscopic Resection of Lung Cancer - Hu JC; Chai XQ; Wang D; Shu SH; Magnussen CG; Xie LX; Hu SS (KARGER, 2022)
Objectives: This study aimed to determine the effect of intraoperative administration of flurbiprofen on postoperative levels of programmed death 1 (PD-1) in patients undergoing thoracoscopic surgery. Materials and Methods: In this prospective double-blind trial, patients were randomized to receive intralipid (control group, n = 34, 0.1 mL/kg, i.v.) or flurbiprofen axetil (flurbiprofen group, n = 34, 50 mg, i.v.) before induction of anesthesia. PD-1 levels on T cell subsets, inflammation, and immune markers in peripheral blood were examined before the induction of anesthesia (T-0) and 24 h (T-1), 72 h (T-2), and 1 week (T-3) after surgery. A linear mixed model was used to determine whether the changes from baseline values (T-0) between groups were significantly different. Results: The increases in the percentage of PD-1((+))CD8((+)) T cells observed at T-1 and T-2 in the control group were higher than those in the flurbiprofen group (T-1: 12.91 +/- 1.65 vs. 7.86 +/- 5.71%, p = 0.031; T-2: 11.54 +/- 1.54 vs. 8.75 +/- 1.73%, p = 0.004), whereas no differences were observed in the changes in the percentage of PD-1((+))CD4((+)) T cells at T-1 and T-2 between the groups. Moreover, extensive changes in the percentage of lymphocyte subsets and inflammatory marker concentrations were observed at T-1 and T-2 after surgery and flurbiprofen attenuated most of these changes. Conclusions: Perioperative administration of flurbiprofen attenuated the postoperative increase in PD-1 levels on CD8((+)) T cells up to 72 h after surgery, but not after this duration. The clinical relevance of changes in PD-1 levels to long-term surgical outcome remains unknown.